1975
DOI: 10.1139/b75-052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helminthosporium maydis race T toxin on protoplasts of resistant and susceptible corn (Zea mays)

Abstract: Leaf protoplasts from resistant (N, C, and S cytoplasm) and susceptible (T cytoplasm) corn inbred W182B (Zea mays L.) exhibited a differential response after exposure to Helminthosporium maydis race T toxin. The volume of untreated protoplasts increased twofold during the first 24 h after isolation and by 48–72 h, most protoplasts exhibited an extensive network of cytoplasmic strands and the chloroplasts were distributed throughout the cytoplasm by cyclosis. However, susceptible protoplasts exposed to ≥2 μg to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…3b and 5). These results are consistent with the observations that N versions of maize are partially toxin-sensitive in the root elongation bioassay (7,20), as well as in other physiological phenomena (4,8,9,22 Root elongation, and thus the physiological age of cells, was found to be an important factor in demonstrating the sensitivity of maize roots to the toxin complex. This was found for both the basal (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3b and 5). These results are consistent with the observations that N versions of maize are partially toxin-sensitive in the root elongation bioassay (7,20), as well as in other physiological phenomena (4,8,9,22 Root elongation, and thus the physiological age of cells, was found to be an important factor in demonstrating the sensitivity of maize roots to the toxin complex. This was found for both the basal (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Wolf and Earle (1990) also found that after HC toxin treatment the number of surviving maize calli varied depending on the genotype . Similar observations have been made by various authors also on different species (Pelcher et al ., 1975 ;Arcioni et al ., 1987 ;Chawla & Wenzel, 1987 ;Binarova et al ., 1990 ;Liu et al ., 1991) . The 2% to 8% regeneration frequency of calli selected on MST medium was approximately ten times lower in average as compared to that under non-toxic conditions .…”
Section: Response Of Wheat Genotypes To In Vitro Selection and Plant supporting
confidence: 93%
“…several Helminthosporiurn toxins (Gengenbach et al, 1977;Ling et al, 1985;Rines & Luke, 1985;Chawla & Wenzel, 1987b). For many host-specific toxins an excellent correlation has been demonstrated between resistance to the pathogen at the plant level and insensitivity to the toxin at the cellular level (Strobel, 1975;Pelcher et al, 1975;Earle, 1982;Gendloff et al, 1987;Ishida & Kumashiro, 1988). However, examples showing that resistance to host-specific toxins was not expressed at the cellular level are also known, e.g.…”
Section: Selection With Phytotoxinsmentioning
confidence: 99%